Trade off Between Military Expenditure and Fixed Capital Formation on Economic Growth: Panel Study of Some SAARC and ASEAN Countries - Dangal, Dil Nath; Gajurel, Ramayan Prasad (Journal of Nepalese Management and Research, 2022)
This paper intends to investigate the relationship between military expenditure and fixed capital formation on economic growth of some SAARC and ASEAN countries including Nepal with balanced yearly panel data of military expenditure (MILEX), gross fixed capital formation (GFCF) and constant GDP as the proxied for the variables of interest over the period of 2001 to 2020. The quantitative strategy is applied to establish the presumed relationship. The paper employs the cross-sectional dependency test, then panel generalized least square (GLS), fully modified ordinary least square (FMOLS), and finally Dumitrescu-Hurlin panel causality approaches. The CD test shows the cross-section dependency among the panel groups. The panel GLS reveals that there is positive relationship between both military expenditure and fixed capital formation on economic growth. However fixed capital formation is more crucial than military expenditure on economic growth. FMOLS suggests that military expenditure and fixed capital formation can promote economic growth but more by fixed capital formation. However, D-H panel causality does not support the view of casual relationship between military expenditure and fixed capital formation on economic growth. But there is unidirectional relationship between economic growth on explanatory variables and there is bidirectional causality between military expenditure and fixed capital formation. The stylized facts suggest to sampled countries that they need to focused on fixed capital formation with maintaining the minimal level of military to accelerate the growth. This paper has an attempt to fill the empirical gaps in Asian countries with Nepal. The updated panel data and comparative studies support to scientific communities cum policy makers of respective countries.